If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 1 = 5x + 13 Reorder the terms: 1 + 3x = 5x + 13 Reorder the terms: 1 + 3x = 13 + 5x Solving 1 + 3x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 3x + -5x = 13 + 5x + -5x Combine like terms: 3x + -5x = -2x 1 + -2x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -2x = 13 + 0 1 + -2x = 13 Add '-1' to each side of the equation. 1 + -1 + -2x = 13 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 13 + -1 -2x = 13 + -1 Combine like terms: 13 + -1 = 12 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| .8y-1.6=4y | | 4x-1(9+-3x)=8x-1 | | a(b+c+11)= | | 7(p+q+4)= | | e(s+t)= | | 2x-4x-13=-2x+7-13 | | 2x-3=6(4x-7) | | 16(y+3)= | | 3x^2-8x-1=0# | | -12x+6=22-4x | | 4(x-2)+4=6x-2(3+x) | | -4(t-4)-(t+3)=5 | | -2a+6=12 | | a(b+8)= | | (11a^5y^10)(-7a^6y^8)=0 | | 2y+.1=3y+.4 | | 20+=60 | | 2(15+q)= | | 6+1/2=22 | | 9(x-4)+3=-33 | | 8=4s+6 | | 4(x-2)-3=(2-x)5 | | 2y^2+7y=-3 | | -(3d+4)=5(2-d) | | 3[x-2]-5x=-2x-6 | | 4(-6v-3)=4-8v | | 9x+2=9x+2 | | 8+0.2b=12 | | 8x^2-24x+18=0 | | 3(n+7)= | | .4x+.7=-.14 | | 3y+5=1.4 |